Extra-role behaviors and job creep: the relationships between affect, withdrawal behaviors and organizational identification - Erden, Nil Selenay (My University, 2015)
Bu çalışmanın amacı, rol ötesi davranışların ve iş taşmasının sonuçlarını araştırmaktadır. Bu doğrultuda kurulan araştırma hipotezleri; rol ötesi davranışların gönüllü sergilendikleri durumda olumlu duygulanımı arttıracağı ve bu olumlu duyguların örgütle özdeşleşmeye katkıda bulunacağıdır. Ancak rol ötesi davranışların gönüllülük esasıyla değil de baskı sonucu sergilenmeleriyle iş taşmasına yol açmaları durumunda, olumsuz duygulanımı ve geri çekilme davranışlarını arttıracakları beklenmiştir. İstanbul’da hizmet sektörü çalışanları üzerinde yapılan bu araştırmanın sonuçları, rol ötesi davranışların olumlu duyguları ve örgütle özdeşleşmeyi; iş taşmasının ise olumsuz duyguları ve geri çekilme davranışlarını arttırdığını göstermiştir. Çalışmanın ana katkısı, literatürde görgül olarak çalışma alanı bulmamış yeni bir değişken olan iş taşmasını ele almasıdır. Böylelikle rol ötesi davranışların ardındaki gönüllülük hususuna dikkat çekilmiştir. Ayrıca rol ötesi davranışların bağımsız değişken olarak ele alınmasının yanı sıra, iki yönlü bir bakış açısı ile hem olumlu hem olumsuz sonuçları incelenmiştir. Temel olarak, iş taşması olgusunun örgütsel davranış alanında yapılan araştırmalarda ele alınabilecek önemli bir husus olduğu ortaya konmuştur. Gelecek çalışmalar için öneriler de sunulmuştur. rol ötesi davranışlar, iş taşması, duygular, geri çekilme davranışları, örgütle özdeşleşme

The aim of this study is to investigate the results of extra-role behaviors and job creep. In this respect, it is hypothesized that when extra-role behaviors are performed voluntarily, they will lead to positive emotions and those positive emotions will contribute to organizational identification. On the other hand, when extra-role behaviors are not performed voluntarily, they will lead to job creep, which will result in negative emotions and employee withdrawal. According to the study conducted on service sector employees working in Istanbul, when performed voluntarily, extra-role behaviors are associated with positive outcomes such as positive emotions and organizational identification. When these behaviors are performed with pressure that leads to job creep, they are associated with negative outcomes such as negative emotions and employee withdrawal. The main contribution of this study is that it investigated a new variable, namely as “job creep.” In this respect, the voluntary aspect of extra-role behaviors is highlighted. In addition to that, this study adopts a fresh perspective by treating extra-role behaviors as an independent variable and focusing on its outcomes. Mainly, it is suggested that job creep could be treated as a sound variable in organizational behavior research. Avenues for future studies are also discussed. extra-role behaviors, job creep, emotions, withdrawal behaviors, organizational identification
Keywords: Örgütsel davranış